A place in the sun at last? The new reading courses for TEIs - Diaz de Rivera, Lina B. (The RAP Journal, 2006)
This paper shares the good news that the new CHED-approved curriculum for pre-service teacher education programs now includes more courses on reading. It specially notes that Developmental Reading 2 focuses on how to teach beginning reading, using the 4-Pronged Approach framework, and hopes that this will better prepare the new teacher for early reading instruction.